BEHAVIOR OF ONLINE SHOPPING THROUGH MOBILE APPLICATION - N., Mahalakshmi; K. M., Devarajanayaka (ShodhKosh: Journal of Visual and Performing Arts, 2024)
One of the most important aspects of our everyday lives is shopping. With a sample size of 100 respondents from various age, educational, and financial groups, this study examines Vijayapura residents’ online shopping habits using mobile applications. Additionally, this study focuses on the behaviour of respondents with respect to the items they prefer to buy, the key elements that influence their decision to shop, and their degree of satisfaction with the goods and services provided by online shopping mobile applications. According to statistical analysis, respondents’ behaviour varies significantly depending on their age, level of education, and budget. The study concludes with the following conclusions: respondents are very satisfied with the goods and services provided on online mobile shopping apps, clothing and footwear items are the most frequently purchased, and product quality and brand are the most significant factors influencing purchase decisions.